ADA settlement exposes liability when providers refuse MAT patients. Issue 6 (8th February 2019) - Enos, Gary
Abstract : A newly announced settlement agreement between the U.S. Department of Justice and a private group medical practice in Virginia serves as a stark reminder that discrimination against individuals with an opioid use disorder (OUD) can interfere with patient access to treatment in the mainstream medical community.